VD_FINDINFO HC / 2014 / 316 vom 11. April 2014 - VD Tribunal cantonal (2014)
OBLIGATION D'ENTRETIEN, CONJOINT, ENFANT, NOUVEAU MOYEN DE PREUVE, TREIZIÈME SALAIRE | 176 al. 1 ch. 1 CC, 317 al. 1 CPC (CH)